Verification of Spatial Heterodyne Spectral Velocimetry Technology Based on Solar Spectrum - Xiang Peng; Mu Gu; Sujun Li; Qifeng Ren; Rujin Zhao (Remote Sensing)
Deep space exploration is one of the key development directions in the aerospace field. With the significant increase in detection distance, the traditional space exploration methods may be ineffective due to effects such as signal energy attenuation and channel delay. There is an urgent need for a miniaturized, quasi-real-time, high-precision space velocity measurement instrument to be mounted on deep space aircraft and provide autonomous navigation. Spatial heterodyne spectral velocimetry technology is a newly proposed high-precision velocimetry method in recent years, and relevant research units have also obtained excellent measurement results in applications. However, this technology originally used laser light sources for active detection, which differs from the passive detection based on stellar light sources required for deep space vehicles in terms of prerequisites. Therefore, this article focuses on the technical route and feasibility exploration of using spatial heterodyne spectral velocimetry technology for stellar absorption spectrum and proposes a practical measurement scheme based on the technical principle of the background light synchronous cancellation method. We measured the radial velocity difference caused by the sun’s rotation at different positions on the solar image plane through outside validation experiments built in a simulated environment on the ground and obtained the experimental data with measurement deviation about 90 m/s and standard deviation about 55 m/s. The experimental results indicate that, under the current stability conditions of ground-based solar observation, we have achieved the same level of measurement accuracy as large ground-based telescopes by using instruments and equipment of much smaller size. It can be considered that the spatial heterodyne spectral velocity measurement scheme proposed in this article has achieved feasibility verification based on stellar spectral detection capability under the premise of instrument miniaturization and quasi-real-time processing. The research content provides a preliminary verification for the development of spatial heterodyne spectral velocimetry technology in the aerospace field and also provides reference for the realization of high-precision autonomous navigation capability in future aerospace technology.